Dançando com a morte: enfrentamento da gripe espanhola no Ceará (1918-1919) (Ágora Journal, 2021)
Knowing the influence of a pandemic in a society allows us to reflect on the success or failure of the measures adopted in coping and to project combat actions in new cases. Based on this premise, the Spanish flu was revisited in the State of Ceará in order to analyze the social impacts caused and the reaction of the authorities and the population. To this end, the advance of the disease in the State, the damage caused to society and the sanitary measures implemented were reassembled. The precariousness of medicines, high prices and uncertainty about their effectiveness were problems faced at the time. Despite establishing actions to contain and cope with the disease, the State and some physicians conducted a disinformation campaign, disregarding the impacts of the disease in order to calm the population and minimize impacts on the economy.